2015
DOI: 10.2967/jnumed.115.154757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Point-Spread Function Modeling on PET Image Quality in Integrated PET/MR Hybrid Imaging

Abstract: The aim of this study was to systematically assess the quantitative and qualitative impact of including point-spread function (PSF) modeling into the process of iterative PET image reconstruction in integrated PET/MR imaging. Methods: All measurements were performed on an integrated whole-body PET/MR system. Three substudies were performed: an 18 F-filled Jaszczak phantom was measured, and the impact of including PSF modeling in ordinary Poisson orderedsubset expectation maximization reconstruction on quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…The effect of PSF modelling was, as expected, larger for smaller tumors, as edge effects are more dominant. Only one other study by Aklan, et al [15] has investigated the quantitative effect of PSF modelling in PET/MR and reported an average increase in SUV mean and SUV max of 21% and 37%, respectively. However, they reported results from generally smaller lesions located at a larger radial distance from the center of transverse FOV, compared to the present study, which may explain the greater impact of the PET PSF modelling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of PSF modelling was, as expected, larger for smaller tumors, as edge effects are more dominant. Only one other study by Aklan, et al [15] has investigated the quantitative effect of PSF modelling in PET/MR and reported an average increase in SUV mean and SUV max of 21% and 37%, respectively. However, they reported results from generally smaller lesions located at a larger radial distance from the center of transverse FOV, compared to the present study, which may explain the greater impact of the PET PSF modelling.…”
Section: Discussionmentioning
confidence: 99%
“…PET images was also reconstructed using PSF modelling (PSF OP-OSEM) with 3 iterations, 21 subsets and 2 mm Gaussian post-filter. The vendor recommends a decrease in Gaussian post filter size from 4 mm to 2 mm when using PSF modelling [15]. All images were reconstructed on 344 × 344 matrices with a pixel size of 2 × 2 mm 2 and slice thickness of 2 mm.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial PET image reconstruction used an iterative ordinary Poisson ordered-subsets expectation maximization algorithm with 21 subsets and 3 iterations incorporating point-spread function resolution modeling (16), a 344 × 344 × 127 matrix, and a 2-mm full-width-at-half-maximum Gaussian post-reconstruction filter. Attenuation correction for the body in the PET reconstruction was estimated using MR imaging (see “Technological Development” section).…”
Section: Methodsmentioning
confidence: 99%
“…(1) Lesions SUV measurements: SUVmax, SUVmean, SUVpeak inside the VOIs, that are the most commonly used semiquantitative parameters for evaluation of tracer uptake; (2) Images Normalized Noise (NN): in the liver ROI, image noise was calculated as the standard deviation divided by the SUVmean in the ROI, as a quantitative evaluation of image quality; 34 (3) Lesions Contrast-to-noise ratio (CNR) was computed for all images as an objective metric of lesion detectability considering image noise around the lesion as defined by Yan et al 23 as…”
Section: Image Metricsmentioning
confidence: 99%